Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Q: Solve the separable differential equation:

$3x - 2y\sqrt{x^2+1}\frac{dy}{dx} = 0$ and subject to the initial condition: $y(0) = 4$. What does $y$ equal, in relation to $x$? I am just really confused what I am suppose to do? Thanks.

share|improve this question
    
This link should help (as a start): en.wikipedia.org/wiki/Separation_of_variables –  t.b. Mar 30 '11 at 21:58
    
Thanks, looking into it right now. –  Mr_CryptoPrime Mar 30 '11 at 22:04
2  
You'll want to subtract the 3x, divide by the square root, and multiply by dx. Then integrate both sides. This is known as the orangoutang method, but it works ;) –  The Chaz 2.0 Mar 30 '11 at 22:08
    
@The Chaz: heh. orangoutang method, never heard that :). This Wikipedia page is worse written than I feared. In brief the recipe is: all $x$'s on one side, all $y$'s on the other and integrate: Write it as $\int_{0}^{t} \frac{3x}{\sqrt{x^2 + 1}}\,dx = \int_{y(0)}^{y(t)} 2y \,dy$. After finishing the integrals let $t = x$. –  t.b. Mar 30 '11 at 22:11
    
Ok, I think I should be able to do it now! I thought they wanted some partial differentiation crap or something, getting way ahead of myself...lol Or is this exactly what this is and I am just being an idiot? –  Mr_CryptoPrime Mar 30 '11 at 22:16

3 Answers 3

up vote 2 down vote accepted

So what we want here is a particular solution to our ODE given our initial condition: $y(0) = 4$

$$3x\ dx = 2y\sqrt{x^{2}+1}\ dy~;\hspace{20 pt} y(0)=4$$

$$\Rightarrow \displaystyle\int 2y\ dy = \displaystyle\int \dfrac{3x}{\sqrt{x^{2}+1}}\ dx$$

$u = x^{2}+1$

$du = 2x\ dx$

$dx = \dfrac{1}{2x}du$

Making the substitutions in for u and dx we see we come to the following:

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = 3 \cdot \dfrac{1}{2} \displaystyle\int \dfrac{x}{\sqrt{u}} \cdot \dfrac{1}{x}\ du$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = \dfrac{3}{2} \displaystyle\int \dfrac{1}{\sqrt{u}}\ du$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = \dfrac{3}{2} \displaystyle\int u^{-\tfrac{1}{2}}\ du$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = \dfrac{3}{2} \cdot 2 ~ u^{\tfrac{1}{2}} + C$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = 3 \sqrt{u}\ du$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y^{2} = 3 \cdot \sqrt{x^{2}+1} + C$

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\Rightarrow y(x) = \displaystyle\pm \sqrt{3} \sqrt[4]{x^{2}+1} + C$

$\underline{\text{Applying Initial Conditions:}}$

$y(0)=4:~~4=\sqrt{3} \displaystyle\sqrt[4]{(0)^{2}+1}~ + C$

$~~~~~~~~~~~~~~~~~~~4=\sqrt{3}\cdot 1~ + C$

$~~~~~~~~~~~~~~~~~~~C=4-\sqrt{3}~\doteq~2.3$

$y(0)=4:~~4=-\sqrt{3} \displaystyle\sqrt[4]{(0)^{2}+1}~ + C$

$~~~~~~~~~~~~~~~~~~~4=-\sqrt{3}\cdot 1~ + C$

$~~~~~~~~~~~~~~~~~~~C=4+\sqrt{3}~\doteq~5.7$

Thus the particular solutions to this separable ODE is,

$~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~~\therefore~~y(x) = \displaystyle \sqrt{3} \sqrt[4]{x^{2}+1} + 2.3 ~~~~\&~~~~ y(x) = \displaystyle -\sqrt{3} \sqrt[4]{x^{2}+1} + 5.7~~~~\blacksquare$

I hope this helped out, and hopefully I did not make any mistakes to cause any type of confusion.

Let me know if there is any step that did not make since to you and I will try and clarify a some more.

Thanks.

Good Luck.

share|improve this answer

Here's what you are supposed to do

$$\int \frac{3x}{\sqrt{x^2+1}}dx = \int 2y dy + C$$

You have a given initial condition and an undetermined constant..

share|improve this answer

[\begin{array}{l} 3x - 2y\sqrt {{x^2} + 1} \frac{{{\rm{d}}y}}{{{\rm{d}}x}} = 0\\ 3x = 2y\sqrt {{x^2} + 1} \frac{{{\rm{d}}y}}{{{\rm{d}}x}}\\ 3\frac{x}{{\sqrt {{x^2} + 1} }} = 2y\frac{{{\rm{d}}y}}{{{\rm{d}}x}}\\ \frac{3}{2}\int_{}^{} {\frac{x}{{\sqrt {{x^2} + 1} }}{\rm{d}}x} = \int_{}^{} {y{\rm{ d}}y} \\ \frac{3}{2}\int_{}^{} {\tan \theta \sec \theta {\rm{ d}}\theta } = \frac{{{y^2}}}{2} + {C_1}\\ \frac{3}{2}\sec \theta + \frac{3}{2}{C_2} = \frac{{{y^2}}}{2} + {C_1}\\ 3\sec \arctan x + C = {y^2}\\ {y^2} = 3\sqrt {1 + {x^2}} + C\\ y = \left( {{\mathop{\rm sgn}} k} \right)\sqrt {3\sqrt {1 + {x^2}} + C} \\ 4 = y(0) = \pm \sqrt {3 + C} \\ 4 = \sqrt {3 + C} \\ C = 13\\ {\mathop{\rm sgn}} k = 1\\ y = \sqrt {3\sqrt {1 + {x^2}} + 13} \end{array}]

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.